Bridging the gap: A systematic review of intraoperative electrocochleography during cochlear implantation and preservation of residual hearing - Jaimee Cooper; Jeenu Mittal; Max Zalta; Nicholas DiStefano; Delany L. Klassen; Keelin McKenna; Dimitri A. Godur; Andrea Monterrubio; Moeed Moosa; Rahul Mittal; Adrien A. Eshraghi (PLoS ONE, 2025)
Cochlear implantation is a surgical intervention to provide auditory rehabilitation to individuals with severe to profound hearing loss. Intraoperative electrocochleography (ECochG) has emerged as a promising tool for monitoring cochlear health during cochlear implant (CI) surgery. This systematic review aims to synthesize current evidence regarding the effectiveness of intraoperative ECochG in predicting postoperative residual hearing levels in CI recipients. A comprehensive literature search was conducted across major databases including PubMed, Embase, Web of Science, and SCOPUS. The protocol for this systematic review was registered in the PROSPERO database (registration number: CRD42023476617). The key outcomes assessed were the correlation between intraoperative ECochG patterns and postoperative residual hearing levels, as well as the influence of surgical techniques and electrode design on ECochG responses and hearing preservation. The Risk of Bias analysis was conducted using the Joanna Briggs Institute Critical Appraisal Tool. The review included a total of eighteen studies that met the inclusion and exclusion criteria. A significant correlation was reported between specific intraoperative ECochG response patterns and the preservation of residual hearing post-surgery. Studies highlighted that robust ECochG responses typically indicated a higher likelihood of postoperative hearing preservation. The review also identified factors influencing ECochG responses, including electrode design and insertion techniques. Several studies reported improved preservation of residual hearing with modifications in surgical approaches guided by ECochG feedback. Intraoperative ECochG monitoring emerges as a crucial tool in predicting and potentially enhancing postoperative residual hearing outcomes in implanted individuals. The review underscores the value of ECochG in guiding surgical technique adjustments, thereby maximizing hearing preservation. However, the heterogeneity in study designs and ECochG protocols suggests a need for standardization in this field. Future research should focus on large-scale, multicenter trials to establish definitive guidelines for integrating ECochG in CI surgeries, with an emphasis on long-term hearing outcomes.